2024
DOI: 10.1021/jacs.3c13060
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Controlled Regiodivergent Nickel-Catalyzed Hydroaminoalkylation of Unactivated Alkenes

Tianze Zhang,
Shan Jiang,
Meng-Ying Qian
et al.

Abstract: Ligand modulation of transition-metal catalysts to achieve optimal reactivity and selectivity in alkene hydrofunctionalization is a fundamental challenge in synthetic organic chemistry. Hydroaminoalkylation, an atom-economical approach for alkylating amines using alkenes, is particularly significant for amine synthesis in the pharmaceutical, agrochemical, and fine chemical industries. However, the existing methods usually require specific substrate combinations to achieve precise regio-and stereoselectivity, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…Again, the Mn-catalyzed cross-coupling reaction of secondary allylic alcohol 1 – 16 with arylketone 2 – 18 and 4-methylbenzaldehyde 2 – 1 could not also bring us the desired α,β-unsaturated carbonyl compounds 4 – 17 and 4 – 18 , respectively. Switching aldehyde 2 – 1 to N -sulfonylimine 2 – 19 only furnish 11% yield of 4 – 1 in steady of β-aminoketone 4 – 19 , possibly due to that N -acylimine 2 – 19 suffered from decomposition to form benzaldehyde again under the standard reaction conditions. Notably, tertiary allylic alcohol 1 – 1 could not react with allylaldehyde 2 – 20 to produce the corresponding α, β, γ, δ-unsaturated ketone 4 – 20 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, the Mn-catalyzed cross-coupling reaction of secondary allylic alcohol 1 – 16 with arylketone 2 – 18 and 4-methylbenzaldehyde 2 – 1 could not also bring us the desired α,β-unsaturated carbonyl compounds 4 – 17 and 4 – 18 , respectively. Switching aldehyde 2 – 1 to N -sulfonylimine 2 – 19 only furnish 11% yield of 4 – 1 in steady of β-aminoketone 4 – 19 , possibly due to that N -acylimine 2 – 19 suffered from decomposition to form benzaldehyde again under the standard reaction conditions. Notably, tertiary allylic alcohol 1 – 1 could not react with allylaldehyde 2 – 20 to produce the corresponding α, β, γ, δ-unsaturated ketone 4 – 20 .…”
Section: Resultsmentioning
confidence: 99%
“…An oven-dried Schlenk tube charged allylic alcohols 1 (0.10 mmol), aldehydes 2 or N -acylimine 2 – 19 (0.20 mmol, 2.0 equiv), Mn­(CO) 5 Br (0.02 mmol, 20 mol %), Me 2 Zn (0.10 mmol, 1.0 equiv), MgO (0.10 mmol, 1.0 equiv), ZnBr 2 (0.10 mmol, 1.0 equiv), and diglyme (0.1 mL) under an Ar atmosphere. The reaction mixture was then allowed to stir at 100 °C (heated by heating mantle) for 4 h. After the reaction mixture was cooled down, the reaction mixture was purified by flash chromatography on silica gel using ethyl acetate/petroleum ether (1:10) as eluent to afford the desired products 3 or 4 .…”
Section: Methodsmentioning
confidence: 99%
“…In 2023, Xiao and co-workers reported a breakthrough: a ligand-controlled, regiodivergent nickel-catalysed hydroaminoalkylation of unactivated alkenes with N -sulfonyl amines (Scheme 54). 137 Tri- tert -butylphosphine facilitates branched regioselectivity and syn diastereoselectivity, while ethyldiphenylphosphine promotes linear selectivity. Systematic evaluations of various monodentate phosphine ligands revealed distinct regioselectivity effects, and %Vbur (min), a steric descriptor of ligands, was identified as a predictive measure of ligand structure's correlation with regioselectivity.…”
Section: Catalytic Transformations Of Simple Alkenes Including Ethyle...mentioning
confidence: 99%
“…To understand the origin of enantioselectivity and regioselectivity, we performed density functional theory (DFT) calculations on the oxidative cyclization of 4-phenyl-1-butene ( 1a ) and imine 2c with nickel (Figure A). This is the step that determines rate, as well as regioselectivity and enantioselectivity (see Supporting Information for details). ,, Calculations of the oxidative cyclization transition states TS1-R and TS1-S showed that the energy for TS1-R was 2.2 kcal/mol lower than that for TS1-S . This difference aligns well with the experimental outcomes, favoring the formation of the ( R )-product.…”
mentioning
confidence: 99%